Theepistemological Foundtion Of Lanage Universals - bouguerra, imadeddine; gahlouz, Abdelkader (El Omda in Linguistics and Discourse Analysis, 2024)
This search work deals with the "affected and influence" supposition between both old and new rational philosophy and modern Universal linguistics aiming for answering and lighting up the epistemological foundation of language Universals in order to know if we could really consider this Universal viewpoint into natural language as an extension of rational philosophical thinking